Kapelan Solidarności [zbiór kart pocztowych z 1987 r.] . The chaplain of Solidarity. Set of postcards from 1987 - B.B. (Polska, 1987)
3 postcards with single-sided, b&w print on white paper, back divided into a notes and address field, including one with imprinted stamp and one with watermark on the front. 3 postcards, issued on the third anniversary of murder of rev. Jerzy Popiełuszko, contain commemorative captions in Polish, English and German, with portraits of the priest (including one in a form of a stamp), his signature, and a graphic image of the Black Madonna of Częstochowa. The watermark carries information about the occasion with date and caption "Chaplain of Solidarity".